(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2015)
What Kentucky writer-farmer-thinker Wendell Berry thinks about agriculture is usually straightforward and clearly identified as such. What he thinks about culture sometimes has to be gleaned from his opinions on other topics. One topic of American culture that he takes on often in an oblique way is education, and his short story “Pray without Ceasing” (Fid, 1992) is a prime example. Many relevant themes of education play out in the story and how Berry tells it, but formal education is never mentioned—the closest we get is the appearance of Jack Beechum’s grade school teacher. Yet Berry himself cited this story as a way to gain insight into how education could better serve our world, and the story connects with his deepest hope for education. The story raises important questions about the relationship between formal education and violence, something Berry has called the “great moral issue of our time” (WI, 2005, p. 145), and the story suggests how education could do better.